Pengaruh Pemberian Tambahan Penghasilan Pegawai Terhadap Kepuasan Kerja dan Implikasinya Pada Peningkatan Kinerja Pegawai - Basuki, Rachmawati Prasetyoning; Sawitri, Dyah; Muawanah, Umi (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Employee performance is a key factor in ensuring high-quality public service delivery. One aspect that influences employee performance is job satisfaction, which reflects a positive feeling toward their work. Job satisfaction can be affected by employee well-being, including financial incentives such as the Employee Income Supplement (TPP). This study aims to analyze the effect of TPP on job satisfaction and employee performance, as well as the role of job satisfaction in mediating the relationship between TPP and employee performance. Using an explanatory research method and a census technique involving 141 employees, the analysis was conducted using SmartPLS. The results show that TPP has a positive and significant effect on job satisfaction, emphasizing the importance of a fair compensation system in enhancing employee well-being. Additionally, TPP positively influences employee performance, indicating that adequate incentives can encourage employees to achieve better results. Job satisfaction is also proven to have a positive effect on performance, as satisfied employees tend to be more dedicated to their work. Furthermore, TPP indirectly affects employee performance through job satisfaction, reinforcing the mediating role of job satisfaction in improving employee productivity.